Personal protective equipment and infection prevention and control: a national survey of UK medical students and interim foundation doctors during the COVID-19 pandemic. (23rd October 2020) - Norton, Emma Jane; Georgiou, Ioannis; Fung, Alex; Nazari, Armin; Bandyopadhyay, Soham; Saunders, Kate E A
Abstract: Background: The adequacy of personal protective equipment (PPE) and infection prevention and control (IPC) training in UK medical students and interim Foundation Year 1 (FiY1) doctors during the COVID-19 pandemic is unknown, as is its impact on COVID-19-related anxiety. Methods: Cross-sectional, multi-centre study analysing self-reported adequacy of PPE and IPC training and correlation to a modified pandemic anxiety scale. Participants were current medical students and FiY1 doctors in the UK. Data were collected by an online survey. Results: Participants reported that they received insufficient PPE information (43%) and IPC training (56%). Significantly, fewer participants identifying as women or BAME/mixed ethnicity reported receiving sufficient PPE information, compared with those identifying as men and White British/White Other, respectively. COVID-19-related anxiety was significantly higher in those without sufficient reported PPE or IPC training, in women compared with men, and in FiY1 doctors compared with medical students. Conclusions: With medical students currently volunteering in and imminently returning to hospitals in an educational capacity, levels of self-reported PPE and IPC training are sub-optimal. Better training is paramount to avoid harm to patients and healthcare professionals and to reduce COVID-19-related anxiety among medical students and FiY1 doctors.